Bug Bounty Hunting Essentials : Quick-paced guide to help white-hat hackers get through bug bounty programs /: Quick-paced guide to help white-hat hackers get through bug bounty programs. (2018) - Lozano, Carlos A; Amir, Shahmeer
No abstract available